Glomus Tumor of the Palate Report of a Case and Review of the Literatures - YAMAMOTO, Gou; MATSUI, Yoshirou; MAEDA, Yukiko; TAKARADA, Mie; NAGUMO, Masao; TACHIKAWA, Tetsuhiko; NAGOSHI, Yuki; IRIE, Tarou; AIDA, Tadateru (The Journal of Showa University Dental Society, 2005)
A Glomus tumour is a benign neoplasm arising from the glomus cells which are located arteriovenous anastomosis in vascular plexus of skin and nail bed. In this paper, we report a case of glomus tumor arising in the palate and review of the literatures. A 21-year-old man presented with swelling measuring 3 cm in diameter in the hard and soft palate. Histopathological examination showed a well-circumscribed nodule formation in submucosa. Tumor cells were uniform shape and composed of solid proliferation with showed the pattern of nonepithelial neoplasm where the individual cells are surrounded by reteticulin fibers. Immunohistochemical staining, vimentin, alpha smooth muscle actin and HHF-35 were positive and keratin, desmin, S-100 protein and factor VIII were negative in tumor cells. Our review of the literature revealed 24 reported cases of glomus tumor and appeared that a predilection of the palate (34.7%), male predominance (1.6 : 1) and slow growth.